If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(b + -2) = -3 Reorder the terms: 3(-2 + b) = -3 (-2 * 3 + b * 3) = -3 (-6 + 3b) = -3 Solving -6 + 3b = -3 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 3b = -3 + 6 Combine like terms: -6 + 6 = 0 0 + 3b = -3 + 6 3b = -3 + 6 Combine like terms: -3 + 6 = 3 3b = 3 Divide each side by '3'. b = 1 Simplifying b = 1
| 3(n+1)=-15 | | (y^7-y^3)-(y^4-y)= | | y-26=3 | | 40x+18x-3=468 | | x^2-6x+y+5=0 | | 3t+17-4t=-18 | | 2v-1=1 | | -1-2x(1-7)=8 | | -36.8+9.2x= | | 18x+40(x-3)=468 | | 3x(x+10)=99 | | 9=n/13 | | (4x-11)-(-16x-17)= | | 4x^2+25y^2-100y=0 | | 3*(-1)+2*2-3x=-2 | | 3(t-4)=-2(t-3)+14 | | (X-4)(x+12)= | | 2x-21=x+4 | | x^2+17=19 | | 40x-18(x-3)=468 | | y+6.2=9.1 | | 63=c-21+2c | | 3/6=/8 | | 16+x=42 | | 3.29-0.223= | | 4t^2-20t-60=0 | | 2sin(30+x)=3cosx | | 2+p=2 | | 5n-6=7 | | ln(x)+ln(1.1675x)=5.28 | | 5x-6=93-6x | | 5t+4=11 |